2023
DOI: 10.1007/s11356-023-27424-0
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil bacterial populations to application of biosolids under short-term flooding

Abstract: Biosolids are applied to agricultural land as a soil conditioner and source of crop nutrients. However, there is concern that bacteria from biosolids may become established in soils, particularly if that soil becomes water-logged. This study examined the microbial community of arable soils cultivated with barley under different applications of biosolids (0, 24t/ha, 48t/ha) in laboratory mesocosms which simulated a 10-day flood. Nutrients (P and N) and organic matter in the soil increased with application rate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Individual investigations have revealed that flooding causes notable changes in microbial activity [17] and the structure of the soil bacterial community [52], including modelling of flooded soils and river water. Nonetheless, there is evidence that the following flooding, microbial community numbers revert to their initial condition in both flood and biosolids application trials [53]. Bacterial communities are also quite stable and recovering from brief floods, according to model tests conducted on organic soil [54].…”
Section: Discussionmentioning
confidence: 99%
“…Individual investigations have revealed that flooding causes notable changes in microbial activity [17] and the structure of the soil bacterial community [52], including modelling of flooded soils and river water. Nonetheless, there is evidence that the following flooding, microbial community numbers revert to their initial condition in both flood and biosolids application trials [53]. Bacterial communities are also quite stable and recovering from brief floods, according to model tests conducted on organic soil [54].…”
Section: Discussionmentioning
confidence: 99%